“Dauntless” Busana dengan Sumber Ide Pavilion Cenghuang - Pertiwi, Zhely; Budiastuti, Emy (Institut Seni Indonesia Padangpanjang, 2023)
The process of creating this artwork is explored as a cultural topic, and ideas are sourced from the Chenghuang Pavilion. The inspiration for this artwork comes from the pavilion, which has a strong Chinese cultural identity. The iconic form of the pavilion and the bold colors present in it add a sense of power, representing a strong and characteristic pavilion. The process of creating this artwork involves several analyses, starting from the mood board, design, calculation, selection of materials and techniques, and design simulation. The process of creating the artwork begins with the search for ideas and concepts from a similar pavilion, which has a similar architectural style and texture to the Chenghuang Pavilion. Until a mature concept is found, the selection of ideas, design, techniques, and creation of the pavilion clothing is carried out. Thus, a suitable artwork is obtained that aligns with the purpose, reasoning, and analysis of why the product was created.